ART, POLITICS AND ENVIRONMENTAL EDUCATION: THE CONTRIBUTION OF THE THEODOR ADORNO'S THINKING - Lemos de Souza, Heluane Aparecida [UNESP]; Feiteiro Cavalari, Rosa Maria [UNESP] (Univ Metodista Piracicaba-unimep, 2020)
The relationship society-nature derives mainly from the conception of nature that we construct or, as Bornheim (1985, p. 18) asserts, how man makes nature present Since Descartes (1596-1650) and Bacon (1561-1626), the scientific knowledge started to have an interventionist function, being necessary the knowledge of nature to dominate it. The Critical Theory elaborated by the Frankfurt School radically opposes to this perspective of knowledge. Similarly, we affirm that the current socio-environmental crisis cannot be solved only through by science and technology, although we cannot give up their contribution, being fundamentally a political concern (BORNHEIM. 1985). Therefore, we understand Education and Art, from a political perspective, essential for the transformation of reality. The objective of this research, that has a qualitative approach and a bibliographical nature, is to analyze the art, from Theodor Adorno's perspective, as well as to identify possible contributions to Environmental Education. We understand that, for Adorno, art is a form of knowledge, that allows an aesthetic experience, and a political praxis. As a form of knowledge, art is, dialectically, mimesis and rationality. Furthermore, art is a condition for establishing with the aesthetic experience of nature, which allows it to be understood as a phenomenon and experienced through the image. Finally, art relates to society not only by its production and origin of its content but, as an autonomous art, occupying a position antagonistic to the society. The art, according to Adorno's conception, can approach Caryalho's proposal (1989, 2006) for EE, according to our understanding.
Keywords: THEODOR ADORNO; ART; ENVIRONMENTAL EDUCATION